2013
DOI: 10.5539/ass.v9n12p252
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Teaching and Learning towards the Satisfaction among the University Students

Abstract: The aim of this study is to examine the relationship between the students' perception of the quality of teaching and learning and their satisfaction in a great university in Indonesia, which was very important in the effort of upgrading the quality of higher education. A survey research involving the sample of 387 students was conducted. The research instruments of the study regarding the quality of teaching and learning consisted of aspects such as the courses, lecturers' motivation, instructional design, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
2
6
0
1
Order By: Relevance
“…This study explored the relationship gender, reasons to participate in STEM-related subjects, programs, and the university supports on first-year university student's satisfaction. The SEM results showed that students' satisfaction with STEM learning is highly affected by university supports (experiences as a student) which is consistent with previous studies that university supports highly correlated with student's overall satisfaction (Crisp et al, 2009;Green, Hood, & Neumann, 2015;Gruber, FuĂź, Voss, & Gläser-Zikuda, 2010;Hakim, 2014;Lo, 2010;Suarman, Aziz, & Yasin, 2013;Wilkins, Balakrishnan, & Huisman, 2012). This result confirms and strengthens the fact that student satisfaction can be used as indicators to identify the areas where the university is performing well.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This study explored the relationship gender, reasons to participate in STEM-related subjects, programs, and the university supports on first-year university student's satisfaction. The SEM results showed that students' satisfaction with STEM learning is highly affected by university supports (experiences as a student) which is consistent with previous studies that university supports highly correlated with student's overall satisfaction (Crisp et al, 2009;Green, Hood, & Neumann, 2015;Gruber, FuĂź, Voss, & Gläser-Zikuda, 2010;Hakim, 2014;Lo, 2010;Suarman, Aziz, & Yasin, 2013;Wilkins, Balakrishnan, & Huisman, 2012). This result confirms and strengthens the fact that student satisfaction can be used as indicators to identify the areas where the university is performing well.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, students in a university STEM classroom probably have different learning needs compared to students in different subject areas, such as laboratory activities or site visits (Chang & Park, 2014). This finding has encouraged STEM teaching to satisfy the students expectation because teaching quality and expertise showed the most reliable relationship with student's satisfaction and their learning outcomes (Green, Hood, & Neumann, 2015;Hakim, 2014;Lo, 2010;Suarman, Aziz, & Yasin, 2013;Burgess, Senior, Moores, 2018;Khalil-Ur-Rehman, Farooq, & Younas, 2018;Son, Ha, Thi, & Khuyen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few components contained in the teaching and learning processes that are the main factors determining the quality of teaching which is consists of the lecturer (motivation, competence, the technique of building rapport with the students), teaching tools (courses, syllabus, media, teaching methods), students (students' competence, relationship among students), and instructional implementation (explanation on lecture materials, task assignment, evaluation, as well as restraints in teaching) (Suarman et al, 2013). According to Marsh (1990), Toland and De Ayala (2005), Gursoy and Umbreit (2005), Oxford Brookes University (2005), there are nine components of the quality of teaching and learning, which are the 1) courses, 2) lecturers' motivation, 3) instructional design, 4) relationship among students, 5) relationship between the students and lecturers, 6) assignment, 7) lecturers' competence, 8) obstacles and constraints, and 9) evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quality teaching is also one of the tools that have a great impact on students' satisfaction. (Suarman et. al, (2013)).…”
mentioning
confidence: 99%
“…Self-efficacy among the teachers is considered one of the prime factors for enhancing the quality of teaching, Suarman (2015). The study of (Suarman et. al, (2013)) stated that assessing the quality of teaching does not only help teachers in their professional development 40 | but also assists in taking the direct measures of students' satisfaction during their learning journey.…”
mentioning
confidence: 99%